Thermal conductivity of a Kondo superconductor in the gapless state - I. M. Tang (2018)
The thermal conductivity coefficient for a Kondo superconductor in the gapless state is obtained within the framework of the Matsuura, Ichinose, and Nagaoka theory. By expanding the heat current correlation function appearing in the Kubo formula for the thermal conductivity in powers of the order parameter, analytical expressions for the thermal conductivity to second power in the order parameter are obtained. The thermal conductivities for both TK≫Tc0 and TK≪Tc0 superconductors are obtained. © 1985 Plenum Publishing Corporation.